New Insights Into the Evolution of Corticotropin-Releasing Hormone Family With a Special Focus on Teleosts - Maugars, Gersende; Mauvois, Xavier; Martin, Patrick; Aroua, Salima; Rousseau, Karine; Dufour, Sylvie (Frontiers in Endocrinology, 2022)
Corticotropin-releasing hormone (CRH) was discovered for its role as a brain neurohormone controlling the corticotropic axis in vertebrates. An additional crh gene, crh2, paralog of crh (crh1), and likely resulting from the second round (2R) of vertebrate whole genome duplication (WGD), was identified in a holocephalan chondrichthyan, in basal mammals, various sauropsids and a non-teleost actinopterygian holostean. It was suggested that crh2 has been recurrently lost in some vertebrate groups including teleosts. We further investigated the fate of crh1 and crh2 in vertebrates with a special focus on teleosts. Phylogenetic and synteny analyses showed the presence of duplicated crh1 paralogs, crh1a and crh1b, in most teleosts, resulting from the teleost-specific WGD (3R). Crh1b is conserved in all teleosts studied, while crh1a has been lost independently in some species. Additional crh1 paralogs are present in carps and salmonids, resulting from specific WGD in these lineages. We identified crh2 gene in additional vertebrate groups such as chondrichthyan elasmobranchs, sarcopterygians including dipnoans and amphibians, and basal actinoperygians, Polypteridae and Chondrostei. We also revealed the presence of crh2 in teleosts, including elopomorphs, osteoglossomorphs, clupeiforms, and ostariophysians, while it would have been lost in Euteleostei along with some other groups. To get some insights on the functional evolution of the crh paralogs, we compared their primary and 3D structure, and by qPCR their tissue distribution, in two representative species, the European eel, which possesses three crh paralogs (crh1a, crh1b, crh2), and the Atlantic salmon, which possesses four crh paralogs of the crh1-type. All peptides conserved the structural characteristics of human CRH. Eel crh1b and both salmon crh1b genes were mainly expressed in the brain, supporting the major role of crh1b paralogs in controlling the corticotropic axis in teleosts. In contrast, crh1a paralogs were mainly expressed in peripheral tissues such as muscle and heart, in eel and salmon, reflecting a striking subfunctionalisation between crh1a and b paralogs. Eel crh2 was weakly expressed in the brain and peripheral tissues. These results revisit the repertoire of crh in teleosts and highlight functional